Comparative assessments for environmental impacts from three advanced asphalt pavement construction cases. (15th May 2021) - Wang, Fusong; Hoff, Inge; Yang, Fei; Wu, Shaopeng; Xie, Jun; Li, Na; Zhang, Lei
Abstract: Applying advanced asphalt pavement technology is a promising trend for future sustainable road construction. However, the environmental impacts of different advanced asphalt pavements remain unclear, thus hindering their future applications. This study presents comparative assessments for the energy consumption and Greenhouse Gas (GHG) emission of advanced asphalt pavement constructions in light of life cycle assessment (LCA), taking three selected cases as representatives for self-healing, steel slag recycling and warm mix technology. A holistic inventory for material and machinery is compiled based on the primary data from construction sites. Afterwards, the environmental assessments of three advanced asphalt pavements are compared from the upper and the overall asphalt layers perspectives, respectively. In addition, the critical sectors during pavement construction are identified based on comparative analysis. The results show that considering the single upper layer, the construction of 1 km self-healing layer causes the most of environmental burdens at 139.51 metric tons of CO2 equivalent and 1.81 TJ of energy consumption; steel slag recycled layer causes the lightest, approximately 60% of self-healing layer's consequences. From the overall asphalt layers perspective, constructing warm mix asphalt pavement is the most environmentally friendly which generates 238.74 metric tons of CO2 equivalent and 3.59 TJ of energy consumption for 1 km. The environmental burdens generated in materials extraction stage occupy considerable percentage with 47.41%–71.29% of CO2 equivalent and 55.08%–73.68% of energy consumption. Recycled materials applications, transport distance managements and located climate conditions are three identified aspects of strikingly affecting environmental impacts of asphalt pavement construction.